Organizational Resilience Strategies in Facing the Post-Pandemic Economy - Ayu Trisanti; Ritawati Sirait; Lestari Pratiwi Sitanggang (JENOVA : Journal of Economics, Finance, Accounting, and Organizational Advancement, 2025)
This study examines the effectiveness of organizational resilience strategies in maintaining revenue stability amid post-COVID-19 economic uncertainty. Employing a quantitative descriptive-correlational design, the study collected data from 200 top managers across various industrial sectors in Indonesia using an online Likert-scale questionnaire, supported by corporate financial reports from 2019 to 2023. Pearson correlation and multiple linear regression analyses were used to assess the relationship between resilience strategies and revenue stability. The findings indicate that all examined strategies have positive and significant effects on revenue stability. Adaptive leadership emerged as the most influential factor, showing the strongest correlation and regression coefficient (r = 0.68; β = 0.37; p < 0.01). Supplier diversification (r = 0.61; β = 0.28) and business process digitalization (r = 0.59; β = 0.23) also contributed substantially, while cash flow management (r = 0.52; β = 0.19) and remote working policies (r = 0.44; β = 0.14) provided significant but relatively smaller effects. The regression model explained 58% of the variance in revenue stability (Adjusted R² = 0.58). This study concludes that adaptive leadership, supplier diversification, digitalization, prudent cash flow management, and flexible work arrangements constitute key organizational resilience practices. The findings contribute to resilience literature by confirming the strategic role of adaptive leadership in sustaining organizational performance during post-pandemic recovery.